Criação de valor em fusões e aquisições na indústria de serviços de telecomunicações: evidências do mercado brasileiro - Pasquini , Renato Sarno (2010)
This dissertation paper seeks to bring evidence on value creation in mergers and acquisitions in the Brazilian market for telecommunications services. For this, it was conducted an event study with 16 transactions that occurred between 2003 and 2009, calculating the cumulative abnormal returns of the stocks of acquiring companies over the long term (18 months after the event). The work also presents a consolidation of similar studies on the telecommunications industry abroad in order to enable comparison of results. Finally, attempts to analyze if the stages of regulatory and antitrust approval have incremental effect on stock returns. The paper concludes that there is evidence of positive and significant abnormal returns in the long-term. However, there was no statistical evidence of incremental effect of regulatory and antitrust approvals on the generation of abnormal returns in the days surrounding the event (-1, 3).